TEACHING 3D DRAWING TECHNIQUES - Qosimova Nilufar Muratjonovna; Mahmudova Sarvinoz Shuhratovna (Bright Mind Publishing, 2025)
This work covers the theoretical foundations and practical stages of teaching students the methodology of drawing in 3D style. The content of 3D graphics, its importance in art and design, its role in the development of spatial imagination and creative thinking are analyzed based on a scientific approach. The methodological part contains simple and practical methods for giving volume, applying light and shadow, applying the laws of perspective, and performing basic operations in digital graphics programs (Blender, SketchUp, etc.). This work serves to form solid skills in 3D visual art and introduce innovative approaches to the modern educational process.